Multiplayer online war simulator based on unity3D and openGL - Azmi, Shameer; Bakhtiar, Fahim; Hossain, Afsana (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.